A cohesive zone model for thermomechanical fatigue. (July 2020) - Abraham, Jeffy; Roth, Stephan; Kuna, Meinhard
Highlights: Creep-fatigue damage interaction through rheological bodies. Influence of damage mechanisms on traction-separation curve. Comparison of lifetime behaviour during isothermal, IP- and OP-TMF. Effect of temperature and dwell period on creep and fatigue damages. Abstract: In this study, a temperature dependent elastic-viscoplastic cohesive zone model is developed to predict the thermomechanical fatigue (TMF) behaviour of superalloys. The theory is based on rheological models enhanced with fatigue and creep damage variables which are micro-mechanically motivated. This cohesive law can capture monotonous, cyclic, thermomechanical, and rate dependent loads. The material model is used to simulate the deformation behaviour and to determine the lifetime for isothermal, in-phase- (IP) and out-of-phase- (OP) TMF loading. The capability of the model to capture phase difference between mechanical and thermal loading is demonstrated, and the effects are analysed.